Fenomenologie jako inscenace - Pinc, Zdeněk (Lidé města, 2006)
The idea of phenomenology as a performance is taken from Bernhard Casper. It implies a strange reality that there is kind of an essential kinship between the discourse of Greek theatre, theatricality in general and philosophical discourse related to the idea of performance. In Greek theatre what is being demonstrated is not shown on the stage but rather on the PROSKÉNION. SKÉNÉ originally means the building from which actors enter the PROSKÉNION, when the roles of the first actor as opposed to the chorus were being separated away. Chorus performs in the orchestra and the entire situation presents time in very peculiar way. In fact, it wants to show that “time“ is somehow included more than once, at least twice. One time is that of the viewer: It is known that the Greek expression “to view” (THEOREIN) and “to be godly” (THEOS) shares common etymology; the term “theatre” (THEATRON) is also derived from that of watching, gazing. The time of a theatre performance represents yet another time scale: In theatre something is presented before one’s eyes, something that happened in another time and in a different way. The mythic topic that is shown primarily is already known to all spectators. In certain sense that is a prerequisite and also that what is happening in the theatre, sense of tragedy is KATHARSIS: Redemption of the viewer through particular understanding of the story. Everything takes place with one important prerequisite: Viewers shall watch what is happening on the SKENE, or hence on the proscenium. They should not attempt to see behind the scene; then their view shall not be obscene. It is very peculiar – if we consider the layout of Greek theatre and how it is arranged – its principal idea is linked to the fact that in every story, in every performance, there is something not to be seen, something not to be performed for a viewer, something that should remain hidden, that constitutes some adumbration of the entire story.